The Use of Virtual Platforms in Teaching Bass Guitar - VITIUC, Alexandr (Studia Universitatis Babes-Bolyai Musica, 2024)
The aim of this article is an empirical study of the effectiveness of learning to play the bass guitar using virtual platforms. The empirical study employed such methods as the non-parametric Student’s t-test, the parametric Levene’s test, SWOT analysis and the interview method, the SPSS Statistics 26 package. The results showed a statistically significant improvement in the academic performance of students in the experimental group (EG) after using digital teaching methods, with an increase in average scores when playing the bass guitar by 6.25 points. Intragroup comparisons showed statistically significant improvements (p-value = .000) in the studied subject in the EG. The conclusions emphasize the importance of using digital learning methods to improve academic performance, offering valuable empirical data for the development of educational practices and the basis for further research in this area. Research prospects are based on the need to develop interactive and multimedia resources in the context of studying different forms of art, which contribute to improving the understanding and involvement of students.